The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0306624x20904703
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Cross-Sectional Validation of the CROPS 14-Item for Juvenile Offenders

Abstract: The Child Report of Posttraumatic Symptoms (CROPS) is an effective 26-item trauma assessment tool. Research has indicated a 14-item version of the CROPS for juvenile offenders with improved predictive accuracy for detecting trauma exposure among male offenders and commensurate accuracy for female offenders. However, the 14-item scale has yet to be validated for juvenile offenders with an established trauma measure. Cross-sectional retrospective data of 74 adjudicated youth (59.5% male) from the original CROPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Conflicting results were rated for three measures: the Trauma Symptom Checklist for Children (TSCC), the Child Report of Posttraumatic Symptoms (CROPS), and the MMPI-A. The CROPS had different methodological ratings across studies, with some reporting an EFA along with acceptable Cronbach values in two studies by Edner et al (2017) and Edner, Glaser et al (2020) , Edner, Piegore et al (2020) , and a combination of good alpha values, but a lack of factor analysis in another study ( Flaherty, 2017 ). Similarly, the MMPI-A was reported by Cashel et al (2000) to have a good Cronbach alpha for the PK subscale, but no available factor analysis and Murray et al (2013) also reported no factor analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Conflicting results were rated for three measures: the Trauma Symptom Checklist for Children (TSCC), the Child Report of Posttraumatic Symptoms (CROPS), and the MMPI-A. The CROPS had different methodological ratings across studies, with some reporting an EFA along with acceptable Cronbach values in two studies by Edner et al (2017) and Edner, Glaser et al (2020) , Edner, Piegore et al (2020) , and a combination of good alpha values, but a lack of factor analysis in another study ( Flaherty, 2017 ). Similarly, the MMPI-A was reported by Cashel et al (2000) to have a good Cronbach alpha for the PK subscale, but no available factor analysis and Murray et al (2013) also reported no factor analysis.…”
Section: Resultsmentioning
confidence: 99%